ChemInform Abstract: Bismuth(III)‐Promoted Acetylation of Thioethers into Thioacetates. Issue 49 (December 2015) - Jevric, Martyn; Petersen, Anne Ugleholdt; Mansoe, Mads; Madsen, Anders Oestergaard; Nielsen, Mogens Broendsted
Abstract: A convenient method is found which allows the conversion of tBu‐thioethers to thioacetates, an important function in various fields of chemistry.